Characterization of the technique "backhandling" in underwater rugby and relation between the speed of execution and goal effectiveness in competitions - Samuel José (VIREF Revista de Educación Física, 2019)
Objective: to identify correlations between the speed of execution and effectiveness of the goal in competitions of the technique of backhandling in underwater rugby players. Method: 59 elite underwater rugby players (20 = Women, 39 = Men) first performed a warm-up, both general and specific, to subsequently make 2 gestures on their more skilful side. The assessment of the execution times was made by photogrammetry. The data of the scorer’s table were consulted on the website of the Federation of Underwater Activities. Results: on average, men develop the gesture with greater speed than Women. In addition, for men, there is a high correlation with the shorter execution time and the annotation index in national competitions and that differs with the women sex.